To identify the trend of agroclimatic variabilities of eastern U. P. - Prince; A. K. Singh; S. R. Mishra; A. N. Mishra; Rajan Chaudhari (The Bioscan, 2025)
This study analyzes the annual trends of maximum temperature, minimum temperature, and rainfall across the agroclimatic zones—NEPZ, EPZ, and Vindhyan zone—of Eastern Uttar Pradesh from 2004 to 2023. Linear trend analysis indicated a consistent rise in both maximum and minimum temperatures, while rainfall exhibited a declining trend across all zones. The Mann-Kendall test was employed to determine the statistical significance of these trends at the district level. Results revealed that maximum temperature trends were significantly increasing in Ayodhya, Mirzapur, and Sonbhadra, while minimum temperature trends were significant in Kushinagar and Sonbhadra. Rainfall trends showed significant increases only in Varanasi and Sonbhadra, with other districts showing no statistically significant changes. The findings suggest emerging climatic shifts that may impact agriculture, requiring climate-resilient strategies tailored to district-specific trends.